2011
DOI: 10.1371/journal.pone.0023788
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cystathionine β-synthase and Cystathionine γ-lyase in Human Pregnant Myometrium and Their Roles in the Control of Uterine Contractility

Abstract: BackgroundHuman uterus undergoes distinct molecular and functional changes during pregnancy and parturition. Hydrogen sulfide (H2S) has recently been shown to play a key role in the control of smooth muscle tension. The role of endogenous H2S produced locally in the control of uterine contractility during labour is unknown.Methodology/Principal FindingsHuman myometrium biopsies were obtained from pregnant women undergoing cesarean section at term. Immunohistochemistry analysis showed that cystathionine-γ-lyase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
44
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 31 publications
5
44
0
3
Order By: Relevance
“…Western blot analysis: Protein extraction and Western blot analysis were performed as described previously. 21) Briefly, rat heart tissues were homogenized in cold T-Per lysis buffer (Pierce). Lysates were quickly sonicated in an ice bath and boiled for 5 minutes at 95°C.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis: Protein extraction and Western blot analysis were performed as described previously. 21) Briefly, rat heart tissues were homogenized in cold T-Per lysis buffer (Pierce). Lysates were quickly sonicated in an ice bath and boiled for 5 minutes at 95°C.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have investigated the functions of CSE/H 2 S in pregnancy. Recently, Patel et al 26,27 demonstrated that both cystathionine β-synthase and CSE are present in human intrauterine tissues and placenta. Given that the placenta is a highly vascular organ, we hypothesize that the dysregulation of the CSE/ H 2 S pathway may contribute to placental abnormalities and a preeclampsia-like condition.…”
mentioning
confidence: 99%
“…These metabolic pathways are expressed in different tissues during development. Thus, Cbs is expressed in liver, pregnant myometrium, and decidual tissue, whereas methionine synthase is expressed in all embryonic tissues, the liver being the primary site of activity for these enzymes (48,51,58).Cbs-deficient [Cbs knockout(KO)] mice develop severe Hhcy and provide an extraordinary tool to evaluate its effects during pregnancy. Embryonic development of homozygous animals lacking the enzyme was normal, but there was low birth weight and increased mortality during the postnatal period.…”
mentioning
confidence: 99%
“…These metabolic pathways are expressed in different tissues during development. Thus, Cbs is expressed in liver, pregnant myometrium, and decidual tissue, whereas methionine synthase is expressed in all embryonic tissues, the liver being the primary site of activity for these enzymes (48,51,58).…”
mentioning
confidence: 99%